Reality, Magic, and Other Lies : Fairy-Tale Film Truths - Greenhill, Pauline (Book collections on Project MUSE., 2020)
"Reality, Magic, and Other Lies: Fairy-Tale Film Truths explores connections and discontinuities between lies and truths in fairy-tale films to directly address the current politics of fairy tale and reality. Since the Enlightenment, notions of magic and wonder have been relegated to the realm of the fanciful, with science and reality understood as objective and true. But the skepticism associated with postmodern thought and critiques from diverse perspectives-including but not limited to anti-racist, decolonial, disability, and feminist theorizing-renders this binary distinction questionable. Further, the precise content of magic and science has shifted through history and across location. Pauline Greenhill offers the idea that fairy tales, particularly through the medium of film, often address those distinctions by making magic real and reality magical"--